La gestión de Recursos Humanos como ventaja competitiva para las Empresas. - Bernal Morales, Erika Vanessa (Universidad Antonio Nariño, 2023)
To guarantee competitiveness in a constantly changing market, companies must find ways to generate competitive advantages, so this documentary review focuses on how human resource management can work as a competitive advantage for organizations nowadays.